Design of 650MHz 2-cell Cavity Cryomodule for the CEPC Accelerator. (April 2019) - Han, Ruixiong; Ge, Rui; Li, Shaopeng; Zhang, Jianqin; Zhai, Jiyuan; Sha, Peng; Sang, Minjing; Ma, Qiang; Mi, Zhenghui
Abstract: The Circular Electron Positron Collider ( CEPC) is a long-term collider project. The 650MHz 2-cell SRF cavity cryomodules will be used for CEPC accelerator. All the cryomodules will be operating at 2 Kelvin of superfluid helium. A CEPC cryomodule houses six 2-cell 650 MHz superconducting cavities, six high power couplers, six mechanical tuners, twelve HOM couplers and two HOM absorbers, et. al. The diameter of vacuum vessel is about 1.4m, and the length from flange to flange about 8 m. The technology of Fast Cool-down and magnetic hygiene are introduced. The static heat load of the whole cryomodule is about 5 watt at 2K. Up to September 2018, the conceptual design of the CEPC cryomodule and the mechanical design of the test cryomodule have been completed.